Breaking the Barrier: Challenges in Hepatitis B Seroprotection Among Dialysis Patients - Ehsan, Saad; Imran, Muhammad; Imran, Urwa; Naqvi, Marzia Ali; Sajjad, Wajiha; Zafar, Zahra; Sabir, Omer (Pakistan Journal of Kidney Diseases, 2025)
The high prevalence of hepatitis B and C in the dialysis population is a significant concern in resource-limited settings. While advances in Hepatitis C treatment have mitigated its severity, Hepatitis B remains a critical challenge despite the availability of vaccination. Methods: A retrospective review of hemodialysis data was conducted to assess seroconversion rates in patients vaccinated against Hepatitis B. All unvaccinated patients initiating hemodialysis were vaccinated using a modified-accelerated schedule of 40 µg inactivated HBsAg (Engerix B) on days 0, 7, 21, and 180 as per institutional policy. Anti-HBs levels >10 mIU/mL were considered indicative of seroprotection. Results: Of the 39 patients with complete data (out of 86), 16 (41%) were negative for Anti-HBs. The mean Anti-HBs level in positive patients was 275 IU/L (±353.98), while it was 2.77 IU/L (±2.71) in negative patients. Conclusion: Despite adherence to a super-accelerated vaccination protocol, a significant proportion of dialysis patients fail to achieve protective Anti-HBs levels, underscoring the need for tailored vaccination strategies and regular monitoring in this vulnerable population.